Transformational Leadership of School Principals in the Implementation of the Independent Curriculum - Sari, Nia Lilik Ayu Nur Indah; Muspawi, Mohamad; Pratama, Linardo (STAI Publisistik Thawalib Jakarta, 2025)
Implementing the Independent Curriculum faces challenges; principals' transformational leadership is needed to improve teacher readiness and performance. This study aims to analyze the principal's transformational leadership implementation in implementing the Merdeka Curriculum at State Senior High School 6, Jambi City by reviewing four main aspects: ideal influence, inspirational motivation, intellectual stimulation, and individual consideration. This research uses qualitative methods with a case study approach through observation, interviews, and documentation of school principals, deputy principal for curriculum, and teachers. The research results show that in the aspect of ideal influence, the school principal has been optimal in providing an example through integrity and commitment. Regarding inspirational motivation, school principals have not been optimal in encouraging teachers to innovate, so learning innovation is still limited. Regarding intellectual stimulation, school principals have not been optimal in encouraging teacher creativity and critical thinking, especially in developing project-based and differentiated learning models. Regarding individual consideration, the principal has been optimal in providing personal support through mentoring and training. Supporting factors include the principal's commitment, training, and adequate facilities. The obstacle faced is the lack of teacher skills in methods. In the Pancasila Student Profile Strengthening Project, conventional methods are still used, and teaching materials are limited. The solutions implemented include regular training, mentoring by young teachers, and collaboration with external parties to support project-based learning.